Soft Tissue Profile Changes Subsequent to Rapid Maxillary Expansion in the Mixed Dentition: A Clinical Study - حسن, عبد الكريم; حفاف, رضوان (Latakia University Journal -Medical Sciences Series, 2021)
Aim: To evaluate the soft tissue profile changes after rapid maxillary expansion using the bonded acrylic splint expander as the only treatment intervention in mixed dentition patients. Background: Rapid maxillary expansion (RME) is a common and reliable procedure for maxillary deficiency treatment in mixed dentition patients. RME skeletal and dento-alveolar effects in the vertical and sagittal plane have been widely discussed. These changes may alter the patient’s esthetical characteristics. The previous studies did not address the RME esthetical effects in mixed dentition patient without the inclusion of other appliances, nor for a significant retention period. The purpose of this study was to describe the soft tissue cephalometric changes after RME as the only treatment intervention in mixed dentition patients. Materials and methods: Eighteen patients aged 6-12 years were included. RME was performed using the bonded acrylic splint expander. The expander was activated one turn per day until the maxillary palatal cusps contacted the mandibular lingual cusps. Patients were followed for six months. Soft tissue alterations were assessed using lateral cephalograms. Five soft tissue variables were used. The mean values were calculated before the treatment and after the retention phase. The therapeutic changes were tested statistically using paired samples T-test. Results: There were no significant differences before and after RME therapy in the facial soft tissue profile. The P-value was greater than 0.05 for all the variables. Conclusion: The skeletal and dento-alveolar changes induced by RME did not influence the soft tissue esthetical characteristics in the short term during the mixed dentition period. RME is a conservative procedure from esthetical perspective.